Undated engraving of Louis XIV of France with his wife (Marie Thérèse... - Auteur inconnu (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Undated engraving of Louis XIV of France with his wife (Marie Thérèse of Austria) with their son, the Dauphin of France by an unknown artist.
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons